Literasi Digital Investor Ritel di Era Disrupsi: Navigasi Keuangan Pribadi dan Pasar Modal Menuju Society 5.0 yang Berkelanjutan - Endro Isnugroho; Sulistiono Sulistiono; Nida Urrahma Hidayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The era of digital disruption has brought significant changes to people's behavior, including investment activities. Retail investors have increasingly easy access to the capital market through digital applications such as Neo HOTs, Bibit, and Stockbit. However, this convenience is not always accompanied by adequate digital financial literacy. This study aims to explore retail investors' experiences using digital investment applications and understand their perceptions of sustainable investing in the Society 5.0 era. The research method used a descriptive qualitative approach with in-depth interviews with a number of active retail investors. The findings indicate that the majority of retail investors are attracted to investing due to ease of access and promotions, but many still make impulsive decisions based on social media trends (fear of missing out/FOMO). A small number of investors are beginning to understand the importance of sustainable investing (ESG), although it has not yet become a primary consideration in investment decisions. This study emphasizes the importance of more targeted digital financial literacy so that people can use technology wisely, maintain personal financial sustainability, and contribute to sustainable development.